Effectiveness of Direct-Acting Antiviral Therapy in Patients With Human Immunodeficiency Virus–Hepatitis C Virus Coinfection in Routine Clinical Care: A Multicenter Study. (23rd March 2019) - Kim, H Nina; Nance, Robin M; Williams-Nguyen, Jessica S; Chris Delaney, J A; Crane, Heidi M; Cachay, Edward R; Martin, Jeffrey; Mathews, W Christopher; Chander, Geetanjali; Franco, Ricardo; Hurt, Christopher B; Geng, Elvin H; et al.
Abstract: Background: Direct-acting antiviral (DAA) therapy have been shown to be highly successful in clinical trials and observational studies, but less is known about treatment success in patients with a high burden of comorbid conditions, including mental health and substance use disorders. We evaluated DAA effectiveness across a broad spectrum of patients with human immunodeficiency virus (HIV)–hepatitis C virus (HCV) coinfection in routine clinical care, including those with psychosocial comorbid conditions. Methods: The primary end point was sustained virologic response (SVR), defined as HCV RNA not detected or <25 IU/mL ≥10 weeks after treatment. We calculated SVR rates and 95% confidence intervals (CIs) in a modified intent-to-treat analysis. We repeated this analysis after multiply imputing missing SVR values. Results: Among 642 DAA-treated patients, 536 had SVR assessments. The median age was 55 years; 79% were men, 59% black, and 32% white. Cirrhosis (fibrosis-4 index>3.25) was present in 24%, and 17% were interferon treatment experienced; 96% had genotype 1 infection and 432 (81%) had received ledipasvir-sofosbuvir. SVR occurred in 96.5% (95% CI, 94.5%–97.9%). Patients who were black, treatment experienced, or cirrhotic all had SVR rates >95%. Patients with depression and/or anxiety, psychotic disorder, illicit drug use, or alcohol use disorder also had high SVR rates, ranging from 95.4% to 96.8%. The only factor associated with lower SVR rate was early discontinuation (77.8%; 95% CI, 52.4%–93.6%). Similar results were seen in multiply imputed data sets. Conclusions: Our study represents a large multicenter examination of DAA therapy in HIV/HCV-coinfected patients. The broad treatment success we observed across this diverse group of patients with significant comorbid conditions is highly affirming and argues for widespread implementation of DAA therapy.